2019
DOI: 10.1021/acssuschemeng.8b06560
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Hierarchically Porous Metal–Organic Frameworks: Facile Synthesis, Mechanism Research, and Application

Abstract: Hierarchically porous metal–organic frameworks (H-MOFs) with nanoscale size can endow them with desired properties in promising applications. However, there has been little research focusing on the nanoscale H-MOFs until now. Herein, a simple and versatile synthetic strategy has been developed to rapidly prepare nanoscale hierarchically porous ZIF-67 (NH-ZIF-67) crystals through employing an organic amine as bifunctional modulator. The as-synthesized nanoscale NH-ZIF-67 exhibited tunable porosity and excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…The textural properties of hierarchical porous ZIF-90_X and C-ZIF-90 are summarized in Table 1. All ZIF-90_X samples exhibited higher BET surface areas (S BET ) and Langmuir surface areas (S Langmuir ) than C-ZIF-90, which can be attributed to the decrease in the crystal size can increase surface areas [36]. Furthermore, all ZIF-90_X showed higher total pore volumes (V total ) and mesopore volumes (V meso ) than C-ZIF-90, confirming the generation of mesopores and macropores in ZIF-90_X samples.…”
Section: Resultsmentioning
confidence: 75%
“…The textural properties of hierarchical porous ZIF-90_X and C-ZIF-90 are summarized in Table 1. All ZIF-90_X samples exhibited higher BET surface areas (S BET ) and Langmuir surface areas (S Langmuir ) than C-ZIF-90, which can be attributed to the decrease in the crystal size can increase surface areas [36]. Furthermore, all ZIF-90_X showed higher total pore volumes (V total ) and mesopore volumes (V meso ) than C-ZIF-90, confirming the generation of mesopores and macropores in ZIF-90_X samples.…”
Section: Resultsmentioning
confidence: 75%
“…The adsorption of malachite green on a range of MOFs has been reported [ 59 , 60 , 61 , 62 ]. Table 3 summarizes the data from studies relevant to the present work.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al found that the absorption capacity of MIL-53(Al) increased after functionalization with amino groups [ 59 ], an increase that can be attributed to hydrogen bond interactions [ 62 ] between the amino groups of the dye molecules and the amino groups of MIL-53(Al)-NH 2 ; the adsorption capacity achieved by this system is, however, rather low (45.2 mg/g in the case of methylene blue and 37.8 mg/g in the case of malachite green). Jin et al prepared a ZIF-67 MOF integrated on a polyacrylonitrile membrane to recover the MOF from water solution at the end of the adsorption process [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…ZIF-300 membrane exhibited 99.21% rejection of heavy metal ions and large water permeate flux, 39.2 L/m 2 •h•bar. Another structure of ZIF having nanoscale hierarchically pores, ZIF-67 (NH-ZIF-67), was developed using a rapid process by employing an organic amine as a biofunctional modulator and accelerator of the nucleation (Li et al, 2019b). This study reflected high rates of adsorption of malachite green (MG) as well as high adsorption capacity of toluene.…”
Section: Summary Of Zif Synthesis and Applicationsmentioning
confidence: 99%